The Hospitality: Does It Affect Audit Independence? Auditor vs. Auditee Perspective - Setiawan, Nanang (Jurnal Riset Akuntansi dan Auditing, 2024)
This paper aims to analyze the impact of hospitality on independence and audit quality based on the viewpoints of the auditor and auditee. This paper is qualitative research with data collection by observation and semi-structured interviews with internal auditors and financial managers (auditees) at multinational companies in Indonesia. The results of the analysis state that there are similarities in views between auditors and auditees regarding hospitality. Auditors consider that hospitality, although it cannot be generalized to all auditors, will not interfere with their independence in the audit process and assessment of audit results. The auditee is also of the view that hospitality is one aspect of service from the "host" to the "guest" with service limited to reasonableness by local customs and culture. The auditor and auditee consider that they are partners who maintain a professional work attitude, and hospitality is one of the media for communication in confirming each finding and conveying the results of the audit. This article contributes to increasing literacy regarding the influence of hospitality on the independence and audit results quality and provides consideration to companies as a basis for policy in responding to providing hospitality to auditors in the audit process.